β-glucan modulates cortisol levels in stressed pacu (Piaractus mesopotamicus) inoculated with heat-killed Aeromonas hydrophila - Marinho de Mello, Mariana Maluli [UNESP]; de Fátima Pereira de Faria, Camila [UNESP]; Zanuzzo, Fábio Sabbadin [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2019)
In this study, we show that β-glucan can modulate cortisol release in fish. We simulated a common situation in aquaculture: the transport of fish followed by contact with an opportunistic pathogen and observed what effect glucan had on the immune and stress response in these conditions. Pacu (Piaractus mesopotamicus) were fed with a diet containing β-glucan (0.1%) for 15 days prior to transport followed by an injection with heat-killed Aeromonas hydrophila. We sampled fish before transport, at arrival and at 3 and 24 h after bacterial injection. β-Glucans are used in aquaculture and have a known immunostimulatory effect, which was observed in this study. The results showed that β-glucan modulated the plasma cortisol levels differently by increasing these levels up to 24 h after transport and preventing the increase caused by bacterial inoculum injection. In addition, β-glucan enhanced the activity of the complement system at 24 h and reduced the monocytes and lymphocytes number in peripheral blood at 3 and 24 h after bacterial inoculation. Our results suggest that β-glucan modulated a bidirectional interaction between the stress and the immune responses. The modulation of cortisol levels and the immunostimulation by β-glucan at different moments in our study suggest the compound has a protective effect by avoiding higher levels of the hormone and improving resistance against bacterial infection in pacu. These results add evidence to support the use of β-glucan as an immunomodulator in the aquaculture industry.
Keywords: Immunomodulation; Immunostimulant; Stress; Transport